1999
DOI: 10.1103/physrevb.59.11818
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-diffraction studies of single crystals ofU2T2In(T=

Abstract: Neutron-diffraction experiments on single crystals of U 2 T 2 In (TϭNi, Pd, Pt͒ verify the noncollinear magnetic structures found with studies of polycrystalline samples, and determine the values of the ordered moments. Compared to the earlier studies, we find the ordered moments on the uranium atoms larger, and no moment associated with the T atoms, in disagreement with one previous study. The TϭPt sample has a large electronic specific heat and does not order magnetically. We give a detailed description of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…a) The simplest types of magnetic structures existing in complex crystals have a single null propagation vector at the centre of the BZ: k = (0, 0, 0) = 0. The Fourier coefficients should be real and can be identified to the magnetic moments directly: (35) This expression tells us that the orientation and magnitudes of the magnetic moments in whatever cell of the crystal are identical to those of the zero-cell. The translational symmetry of the magnetic structure 00010-p.13…”
Section: Contribution Of Symmetries In Condensed Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…a) The simplest types of magnetic structures existing in complex crystals have a single null propagation vector at the centre of the BZ: k = (0, 0, 0) = 0. The Fourier coefficients should be real and can be identified to the magnetic moments directly: (35) This expression tells us that the orientation and magnitudes of the magnetic moments in whatever cell of the crystal are identical to those of the zero-cell. The translational symmetry of the magnetic structure 00010-p.13…”
Section: Contribution Of Symmetries In Condensed Mattermentioning
confidence: 99%
“…The R 2 T 2 X compounds, with R = Rare-Earth or Uranium, T = Fe, Co, Ni, Ru, Rh or Pd and X = Sn or In, crystallise in the tetragonal U 3 Si 2 -type crystal structure with space group P 4/mbm [30][31][32][33][34][35]. The occupied Wyckoff positions are (4h) R: (x R , 1/2 + x R , ); (4g) T: (x T , 1/2 + x T , 0) and X: (2a) (0, 0, 0).…”
Section: Symmetry Analysis Of the Commensurate Magnetic Structures Ofmentioning
confidence: 99%
“…High ρ 0 -values normally indicate significant crystallographic disorder. However, as mentioned in the previous section, single-crystal x-ray [3] and neutron-diffraction [20] experiments do not confirm the presence of significant disorder. Transport experiments in a magnetic field lead to a reduction of ρ 0 , which indicates that at least part of the high ρ 0 -value is intrinsic and not due to defects and/or impurities [7].…”
Section: Methodsmentioning
confidence: 75%
“…of the order of 100 µΩcm, which normally indicates significant crystallographic disorder. However, Rietveld analyses of the diffraction patterns obtained by single-crystal x-ray [3] and neutron-diffraction [20], do not confirm the presence of significant disorder. In fact, the refinement factors are good and exclude significant Pt-In site inversion.…”
Section: Introductionmentioning
confidence: 87%
“…[3] neutron diffraction data for U 2 Ni 2 In is fitted for several magnetic configurations. The best fit is achieved, if only the U moment is considered, for G 3 structure with m U ¼ 0:918 m B =U: We performed calculations for the same structures and for the nonmagnetic case and concluded that G 3 structure has lowest E total ; 7 mRy lower than the nonmagnetic state, with an U moment of 0:6 m B =U which is in good agreement with the experimental result.…”
Section: Theory and Calculationsmentioning
confidence: 99%